The Influence of Teacher Attachment Quality on Academic Achievement and Social Skills of Muhammadiyah Pahandut Palangka Raya Primary Students - Sapari, Alpian; Kartini, Nurul Hikmah; Zannah, Fathul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: The background contains the problems or topics studied in this research. Aim: This research aims to explore and analyze the influence of the quality of closeness between students and teachers on students' academic achievement and social skills at the Muhammadiyah Pahandut Palangka Raya Elementary School. Method: This research uses a quantitative approach by collecting data through questionnaires distributed to students and teachers at the elementary school. Results and Dıscussion: The research results show that the quality of the attachment between students and teachers has a significant impact on students' academic achievement and social skills. There is a strong correlation between a good relationship between students and teachers and students' academic achievement and social abilities. These findings provide a deeper understanding of the importance of positive relationships between teachers and students in improving students' learning achievement and social interaction abilities in the educational environment. Conclusion: This research provides a basis for further attention to efforts to develop close relationships between teachers and students as an important factor in improving the quality of education at Elementary School Muhammadiyah Pahandut Palangka Raya.